Analisis Yuridis Mengenai Strategi Dosen Terkait Dengan Mutu Pembelajaran Di Perguruan Tinggi Masa Era New Normal - Halimatul Maryani (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
The scope of education is the parties that are involved in the sphere of education such as proteges/students/college students, the basic and the purpose of education itself, educators, educational materials, educational methods, educational evaluation, educational tools and the surrounding environment within the scope of education. Education is also one of the most important parts of human life that has provisions that aim to help the improvement of living standard and life for themselves and for the country. If referring to the Article 31 (amendment) paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states that "Every citizen has the right to education, of course education is meant in principle, learning what we know is based on face to face in the class. to transfer the knowledge to their students (students / college students). This has now turned into virtual, distance learning, due to various constraints of limited facilities and infrastructure, the ability to absorb the technology, on the other hand, the unstable condition of the spread of covid-19 has certainly become a dilemma for several universities, including the university of Muslim Nusantara Al Washliyah in implementing learning whether it's pure online use organized with Distance Learning (PJJ) -virtual and other types of virtual.Keywords : Strategy, the Quality of Learning,New Normal